BEBAN PAJAK, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP KEPUTUSAN TRANSFER PRICING PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2019 - Yasmin Miranty; Citra Kharisma Utami; Dela Triana Sanubari (Jurnal Akuntansi, Auditing dan Keuangan Syariah, 2022)
Transfer pricing is a company policy in determining the price of a transaction with related parties. The variables of tax expense, firm size and profitability are estimated to have an influence on transfer pricing decisions. This study aims to determine the effect of tax expense, firm size and profitability on transfer pricing decisions which are proxied by the value of related party receivables, while the independent variables in this study are tax expense, firm size and profitability. This study uses secondary data in annual reports published by companies on the Indonesia Stock Exchange. The population in this study are mining companies listed on the Indonesia Stock Exchange for the 2015-2019 period, which are 47 companies. The research method used is non-probability sampling with purposive sampling technique in order to obtain a total sample of 11 companies. The data analysis methods used include: descriptive statistics, classical assumption test and hypothesis testing. The results show that based on the partial test, the tax expense has an effect on transfer pricing decisions with a value of 0.003, firm size affects transfer pricing decisions with a value of 0.002, and profitability has no effect on transfer pricing decisions with a value of 0.281. Meanwhile, the results of the simultaneous test obtained a value of 0.006, meaning that the tax expense, firm size and profitability have a joint effect on transfer pricing decisions. The coefficient of determination is 0.168, which means that 16.8% of transfer pricing is influenced by this variable and the rest is influenced by other variables.